Diseño de una planta para desorción de carbón activado por el método zadra , en sominur Cía. Ltda.Ubicada en el Distrito Minero Bella Rica. - Pineda Tinoco, Maryuri Adela (2015)
The current work has as a main target the design of the desorption area in the gold mining company SOMINUR S.A., which is dedicated to the gold extraction. In this plant is used hydrometallurgical process, one of them is about desorption of gold from pregnant activated carbon came from the adsorption process. The desorption is the elution of gold in an elution tower to 80-90 Celsius degrees, to then it be concentrated in an electro winning cells.